Direct In Vitro Regeneration of Fig (Ficus carica L. CV. Benaty) from Apical and Lateral Buds - Toma, Rafail S.; Tamer, Yousif S. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Benaty fig plant was successfully propagated by tissue culture technique and a reproducible and reliable micropropagation protocol was developed through this investigation. At initiation stage, healthy aseptic cultures from lateral and terminal bud explants of about 85% were achieved when the explants were treated with 0.15% HgCl 2 for 7 minutes. A combined solution of ascorbic acid and citric acid (100 and 150 mgl -1 ) was successfully used to overcome the problem of phenolic compounds exudation from the explants into the culture media. At shoot multiplication stage, the addition of 2.0 mgl - 1 from both BA and kinetin gave the highest number of shoots per explant estimated at 2.66 and 3.33 shoots/ explant respectively. As well as, activated charcoal promoted shoots multiplication in all multiplication parameters. The highest number of shoots per explants (5 shoots/ explant) was obtained on MS medium containing 4.0 gl -1 AC. At root formation stage, the interaction treatment of full MS salt strength with the use of 0.25 mgl -1 NAA gave the highest rooting percentage reaching 87.5%. The highest number of roots (18.5 roots/ explant) was recorded as well from the combined treatment of full MS salt strength with the use of 0.25 mgl -1 NAA. While the longest roots (6.66 cm) were recorded from the interaction treatment of half salt strength and 0.50 mgl -1 IBA. The addition of activated charcoal to the rooting culture medium decreased the rooting percentage from 87.5% at control treatment to 50% and 62.5% when 2.0 and 4.0 gl -1 AC were respectively added. The in vitro propagated fig plantlets were gradually moved in a successful way from lab to field conditions with 95% survival rate.
Keywords: Ficus carica L; in vitro; micropropagation; activated charcoal